MODERN METHODS AND TECHNOLOGIES OF ROLE PLAY IN TEACHING DIALOGUE - Bazarova Sh. A; Alimbaeva I. M. (Galaxy International Interdisciplinary Research Journal, 2021)
In an RPG, it is necessary to distinguish between plot and content. The plot of the game is the area of reality that is reproduced by the students in the game. The plots of games can be very diverse, but they must reflect specific conditions in life, i.e. the game uses certain real (or close to them) situations.